Fiber and ash content of fermented palm oil fronds using liquid organic supplements as potential feed ingredients for ruminant - Said Mirza Pratama; Abdullah Dahlan; Yulia Annisa; Raichan Izzati; Muhammad Resthu (Aceh Journal of Animal Science, 2023)
Inadequate feed causes low productivity of livestock, which is indicated by a slow rate of development and low body weight. Alternative non-conventional feed ingredients derived from oil palm waste have shown the potential to be used as livestock feed. Therefore, this study aimed to evaluate the fiber and ash content of palm fronds fermented with liquid organic supplements. The waste raw material was obtained after grinding the palm fronds and followed by a fermentation process using liquid organic supplements. This process was continued with fiber and ash analysis at the Laboratory of Nutrition Science and Feed Technology, Faculty of Agriculture, Syiah Kuala University. A complete randomized design was employed with four treatments using liquid organic supplements at levels of 0%, 4%, 6%, and 8%, with four replications. The measured parameters were water content, crude fiber, ash, and nitrogen-free extract (NFE). The results showed that the addition of liquid organic supplements had no significant effect (P0.05) on the levels of crude fiber, ash, NFE, and water content. Among all treatments, the results were observed in the P3 treatment (8%) which had the lowest crude fiber content and ash content, namely 22 ± 0.589 and 3.72 ± 0.112, as well as had the highest NFE and water content of 78.15 ± 0.501 and 57.9 ± 0.304, respectively. This indicated that the use of liquid organic supplements had the potential to improve the quality of oil palm midrib fiber and positively impact animal feed.